SEJARAH PENGELOLAAN ZAKAT DI DUNIA MUSLIM DAN INDONESIA (Pendekatan Teori Investigasi-Sejarah Charles Peirce dan Defisit Kebenaran Lieven Boeve) - Faisal, Faisal (Analisis: Jurnal Studi Keislaman, 2011)
Throughout the history of human life, poverty is a “plot of story” that could never be erased, and the history of human life is inevitably not free from the history of how people try various ways to overcome this problem. Alms giving (zakat) is one solution that Islam called upon to remove poverty and economic inequalities. Classical as well as Modern Islamic World has enacted various laws and run variety of alms (zakat) management patterns in order to alleviate such poverty. This article covers the application of such charity in the long history of alms giving, since the classical age of Islam to the realities of current application in modern   times   in   some   Islamic   countries,   with   main   focus,   the application  of  alms  in  Indonesia.  By  using  historical  investigation theory of Charles Peirce and truth deficit of Lieven Boeve, the authors  found  a  number  of  polarization  on  the  practices  of  alms withdrawal and its management in Indonesia which further led to a deficit or a reduction in the role and function of such alms itself, which once reached the golden age in the heyday of Islam. This happens due to many factors, including the ineffectiveness of the implementation of the Law of alms (zakat), the lack of trust in the institution of zakat, and the lack of awareness of those compulsory Muslims to give alm. Overcoming such a deficit, it needs integral and solid steps of thestate and society in the spirit of recontectualization of zakat.